Frequency and risk factors of retinopathy of prematurity in preterm babies at a tertiary care hospital in Lahore: Frequency and risk factors of Retinopathy of prematurity in preterm babies (Journal of Fatima Jinnah Medical University, 2020)
Background: Retinopathy of prematurity (ROP) is a serious but preventable morbidity, leading to childhood blindness. The aim of this study was to analyze the incidence and risk factors of ROP in preterm babies.Subjects and methods: A prospective cohort study was conducted at Neonatology Unit, Hameed Latif Hospital, Lahore, from July 2017 to February 2019. All preterm babies born at Hameed Latif Hospital at ≤ 34 weeks of gestation, birth weight of
Keywords: Preterm infants; Morbidity; Retinopathy of prematurity